Research on Financial Internal Control of W Company - Wang, Mo; Lakkanawanit, Pankaewta (Science, Technology, and Social Sciences Procedia, 2021)
This paper mainly adopts the method of qualitative research, combined with international and domestic literature, W company was selected as the object for field investigation, combined with the basic situation and industry characteristics of W company, this paper studies the current situation of financial internal control and existing problems of W company. The research process theoretically uses the COSO framework to study the financial internal control of W company. It is found that the internal control problems of W company mainly focus on: The control environment is not ideal; weak risk management ability; financial control activities need to be improved; the level of financial internal control information and communication needs to be improved; lack of financial internal control and supervision. These problems affect the development of W company to a certain extent. Therefore, financial internal control is an important component of enterprise development, and enterprises must pay attention to it.